Nursing Care for Mr. S Families with Diabetes Mellitus in The Village of Padamara, Mipiran District, Purbalingga District - Alfiana, Unik; Maryoto, Madyo (Viva Medika, 2023)
Diabetes Mellitus (DM) is a non-communicable disease. According to World Health Organization in 2021, it is a chronic disease caused by the pancreas that is not producing enough insulin or it is caused by the body that is not using the generated insulin effectively. Insulin is a hormone regulating blood glucose. One of the complications of Diabetes Mellitus is neuropathy, indicated by pain, tingling, and numbness. The possible treatment for this symptom in DM patients is by doing regular exercise for 30 minutes three until four times a week such as foot exercise. Physical activity can transport glucose into the cell and increase insulin sensitivity. The research was carried out from Monday, 31st October 2022 to Monday, 7th November 2022. The result of this study showed that on the third day Mrs. K presented a better condition in which she could follow the movement in diabetic foot exercise well and her feet were getting more comfortable; tingling and numbness were not frequently felt.